In vitro mechanistic and in vivo anti-tumor studies of Glycosmis pentaphylla (Retz.) DC against breast cancer. (20th June 2016) - Shoja, M.H.; Reddy, Neetinkumar D.; Nayak, Pawan G.; Biswas, Subhankar; Srinivasan, K.K.; Rao, C. Mallikarjuna
Abstract: Ethnopharmacological relevance: Glycosmis pentaphylla (Retz.) DC (Rutaceae) has been traditionally used for the treatment of rheumatism, cancer, liver disorders, inflammation etc. Aim of the study: The present study is aimed at elucidating the effect of Glycosmis pentaphylla (Retz.) DC on the key markers of apoptosis, metastasis and angiogenesis, in vitro . The study also evaluated the effect of fractions in vivo in DMBA-induced mammary tumor model. Materials and methods: Fractions of Glycosmis pentaphylla (Retz.) DC leaf extracts was studied for their effect on apoptotic markers in breast cancer cell lines, MCF-7 and MDA-MB-231 cells. They were also studied for their effect on metastatic and angiogenic markers, MMP-9 and HIF-1α in MCF-7 cells. The fractions were studied in vivo in DMBA-induced mammary tumor model in Sprague Dawley rats. Results: The studies showed that the fractions induced apoptosis in breast cancer cells through the intrinsic/mitochondrial apoptotic pathway. The fractions were also able to inhibit the metastatic and angiogenic markers, MMP-9 and HIF-1α. Anti-tumor studies in DMBA-induced mammary model in Sprague Dawley rats also showed favorable results. Graphical abstract: